2008
DOI: 10.1057/jdhf.2008.22
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trading volume on stock price volatility in the Arab economy

Abstract: This study intends to examine the price-volume movements in the Arab stock markets, in order to determine the impact of changes in trade volume on the volatility of stock prices as expressed by the unified AMF stock price index. The research covers a sample of eight out of the 15 Arab stock markets included in the Arab Monetary Fund database, using monthly data from 1994 to 2006. The study found that there is an increase in both trading volume and stock price volatility, which may be considered a recent phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(27 reference statements)
5
14
0
1
Order By: Relevance
“…In addition, the study provides evidence of a positive and significant effect of return volatility on trading volume. These results are similar to the findings of Sabri (2008), Mubarik & Javid (2009), Tripathy (2011), Pathirawasam (2011), and Al-Jafari & Tliti (2013. Likewise, the study finds a significant and a positive effect of trading volume on stock returns.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the study provides evidence of a positive and significant effect of return volatility on trading volume. These results are similar to the findings of Sabri (2008), Mubarik & Javid (2009), Tripathy (2011), Pathirawasam (2011), and Al-Jafari & Tliti (2013. Likewise, the study finds a significant and a positive effect of trading volume on stock returns.…”
Section: Resultssupporting
confidence: 90%
“…They found evidence of asymmetry and concluded that trading volumes are higher in a rising market. On the other hand, Sabri (2008) examined eight Arab stock markets and found that volume and prices are significantly integrated and volume volatility represents the most predicted variable of increasing price volatility. However, the correlation between volume and price movements was higher in the stock markets of oil Arab countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their empirical results support the predictions of the model on the nature of the dynamic volume-return relation. De Medeiros and Doornik (2006), Zolontoy and Melenberg (2007) and Sabri (2008) also investigated the empirical relationship between stock returns, return volatility and trading volume in the various stock markets and found the support for a contemporaneous as well as dynamic relationship between the stock returns and trading volume. Mahajan and Singh (2009) studied the relationship between return, volume and volatility dynamics by using Indian sensitivity index Sensex and evidenced the presence of sequential arrival of information due to the direction of causality from volatility to volume.…”
Section: Introductionmentioning
confidence: 98%
“…The information implied from derivative prices are about the risk-neutral distribution of the underlying asset. Bhuyan and Chaudhury [25] [28] examined the impact of change in trade volume on volatility of stock prices as expressed by unified Arab Monetary fund stock price index. He reported increase in both trading volume & stock price volatility.…”
Section: Review Of Literaturementioning
confidence: 99%